Hydration process and microstructure evolution of low exothermic concrete produced with urea. (10th July 2020) - Wang, Li-guo; Ju, Si-yi; Chu, Hong-yan; Liu, Zhi-yong; Yang, Zhi-qiang; Wang, Feng-juan; Jiang, Jin-yang
Highlights: Urea has a significant inhibitory effect on early hydration of cement. The influence of urea on concrete compressive strength is dependent on the concrete age. Calcium carbonate and recrystallization are important reasons for reducing the shrinkage of concrete. Excessive urea content can cause recrystallization in concrete, which may affect the durability of concrete. Abstract: In this paper, the feasibility of using urea as an additive to prepare low exothermic concrete is studied. The effect of different urea contents (0%, 5%, 10%, 15%) urea on the hydration process and the microstructure of the cementitious materials were investigated systematically. The experimental results show that urea has an obvious retarding effect on the early hydration of cement. The curve of the hydration heat release was significantly reduced and delayed with the urea content increased. The early strength of the concrete decreased significantly. Urea has almost no effect on the compressive strength of concrete at 28 days of age. The actual water-to-binder ratio is lowered, and the hygroscopicity and recrystallization of urea are the main reasons for shrinkage reduction and even micro-expansion of concrete. Scanning electron microscope (SEM) and X-ray diffractometer (XRD) results show that urea does not change the cement hydration products. The total amount of chemically bound water and the degree of hydration of the sample show that urea has a greater inhibitory effect on early hydration of cement and less effect on hydration in a later stage. The results of mercury intrusion porosimetry (MIP) show that the total porosity of cement paste has a consistent trend with mechanical properties. When the content of urea in concrete exceeds 10%, white crystals appear inside of concrete. The Fourier Transform Infrared Spectrometry (FT-IR), Differential thermal analysis (TG-DSC) and SEM result show that crystalline product is produced by urea crystallization.